Reclaiming the Past in Post-War Italian Art: Cultural Memory in Arte Povera, 1964–1974 - Minnucci, Roberta (2021)
Arte Povera is conventionally presented as an artistic neo-avant-garde, defined by notions of rupture and originality, and characterised by an anti-establishment and political stance. However, this interpretation, shaped by the critic Germano Celant, does not account for the sustained dialogue with cultural heritage in the oeuvres of some of the artists associated with Arte Povera, before, during and after the historic years of the group (1967¬–1971). Although the quotational aspect of Arte Povera was retrospectively acknowledged by Celant in the 1980s, its existence in the previous decades remains underexplored, as it undermines the cohesion of the group and conflicts with its conventional interpretation. By examining the work of the Arte Povera artists who most consistently engaged with the past — Luciano Fabro, Jannis Kounellis, Giulio Paolini, Pino Pascali and Michelangelo Pistoletto — this thesis investigates the significance of their complex system of cultural references, reconnecting the group with the historical and cultural context of the period. In the face of rapid cultural and social changes, I argue that these artists employed references to art history, classical antiquity, literature and embodied practices to restore continuity with a cultural heritage which had been severely damaged by the war and which was endangered by the uncontrolled development of the emerging capitalistic society. Within the international artistic context of the period, tradition was employed to reclaim an Italian and European cultural identity, which could oppose the expansion of American Pop Art, seen as a celebration of mass consumption society, and Minimal Art, condemned for its detachment from historical and cultural context. These artists reclaimed an endangered past through an Italian and European cultural memory, in a perspective of continuity influenced by multiple temporalities and superimpositions. By foregrounding the artworks themselves, alongside alternative exhibition histories, my thesis makes an innovative contribution to scholarship on Italian post-war art, providing a more nuanced reading of practices within Arte Povera, and re-evaluating its relationship to American art. In addition, it proposes new interpretative pathways for the analysis of the survival of tradition in contemporary art, claiming a reciprocal influence between past and present, and considering their interaction as a vital force for future developments.